Changes in body composition during the macrocycle of professional football players in relation to sports nutrition knowledge - Staśkiewicz, Wiktoria; Grochowska-Niedworok, Elzbieta; Zydek, Grzegorz; Białek-Dratwa, Agnieszka; Grajek, Mateusz; Jaruga-Sȩkowska, Sylwia; Kowalski, Oskar; Kardas, Marek (Frontiers in Nutrition, 2022)
Professional football players are obligated to meet the physical demands and maintain the best possible performance throughout the whole macrocycle. It is important to assess the players' nutrition knowledge, identify areas that require increased nutrition awareness and identify the impact of knowledge on changes in body composition as this can affect the players' health and performance. This study aimed to assess changes in body composition of professional football players during the macrocycle of the spring round of the football championship and to identify the correlation between nutrition knowledge and maintaining body composition. The study included 38 football players. The players' body compositions were analyzed 6 times during the macrocycle consisting of preparatory, competitive, and transition periods using the Direct Segmental Multi-Frequency Bioelectrical Impedance Analysis method. Athletes completed the Nutrition for Sport Knowledge Questionnaire to assess their nutrition knowledge. During the preparatory period, a statistically significant negative correlation was demonstrated between the players' knowledge of the subsections of micronutrients in the diet and the dispersion of the adipose percentage tissue content (r=-0.36, p=0.03). In the competitive period, there was a statistically significant negative correlation between the players' knowledge of sports nutrition and the dispersion of lean body mass (r=-0.46, p=0.004), and skeletal muscle mass (r=-0.36, p=0.03). During the transition period, a statistically significant negative correlation between the players' knowledge of weight control and the dispersion of body mass (r=-0.47, p=0.00) and BMI values (r=-0.48, p=0.00) was identified. The player's knowledge of the subsection of macronutrients significantly negatively correlated with the dispersion of skeletal muscle mass content (r=-0.33, p=0.05). Nutrition knowledge has an impact on the stability of body composition during all analyzed periods: preparatory, competitive, and transition periods.